Psychometric Evaluation of the ACHIEVE Assessment - Crowe, Miriam; Maciver, Donald; Rush, Robert; Forsyth, Kirsty (Frontiers in Pediatrics, 2020)
Objective: There has been a significant change within clinical practice in childhood disability from ‘treating’ at the level of body function to ecological approaches that address the child’s involvement in everyday life. Clinical assessment, and robust tools to support this, are of key importance. The aim of this study was to assess the psychometric properties of the ACHIEVE Assessment in a clinical dataset. The ACHIEVE assessment is a parent and teacher report of participation in home, school and community settings, important contributory factors for participation, and environmental factors. Design: ACHIEVE scores of children were collected from parents and teachers. The Rasch Rating Scale Model produced model estimates with WINSTEPS software. Setting: Clinical rehabilitation settings in Scotland (United Kingdom). Subjects: 401 parents and 335 teachers of 402 children participated resulting in a final sample of 736 responses. Children (78% male) were 4-17 years old (mean 7.91 years SD 2.61). Children had a range of disabilities including Developmental Coordination Disorder, Autism Spectrum Disorder, and Attention Deficit Hyperactivity Disorder. Results: The study includes a large clinical sample of children with disabilities. The results demonstrate that the ACHIEVE Assessment can provide unidimensional measurements of children’s participation and important contributory factors for participation. Differential item functioning analysis indicated majority of items were comparable between parent and teacher report. Conclusions: The results confirm evidence of appropriate psychometric properties of the ACHIEVE Assessment. ACHIEVE is a comprehensive tool that enables identification of patterns and issues around participation for clinical and research purposes.